Pseudoepitheliomatous keratotic and micaceous balanitis: a series of eight cases. (29th June 2022) - Spencer, A.; Watchorn, R.E.; Kravvas, G.; Ben‐Salha, I.; Haider, A.; Francis, N.; Freeman, A.; Alnajjar, H.M.; Muneer, A.; Bunker, C.B.
Abstract: Background: Pseudoepitheliomatous keratotic and micaceous balanitis (PEKMB) is a clinicopathological entity characterized clinically by micaceous scale on the glans, and histologically by acanthosis, hyperkeratosis and pseudoepitheliomatous hyperplasia. We present a series of eight cases of this rare condition, the first series of more than two cases to be reported. Objectives: To determine the clinical and histological characteristics of cases of PEKMB, and evaluate treatments used and clinical course. Methods: This monocentric case series was conducted at the University College London Hospitals tertiary male genital dermatology clinic between April 2018 and August 2020. Eight patients with PEKMB were evaluated. Data were collected on demographics, clinical presentation, histological features, presence of human papilloma virus (HPV), history of lichen sclerosus, treatment of PEKMB and subsequent response, and presence or development of squamous cell carcinoma (SCC) or penile intraepithelial neoplasia (PeIN) during follow‐up. Results: Eight Caucasian males presented with clinical and histological evidence of PEKMB. Seven had a background of lichen sclerosus; two had failed treatment with superpotent topical steroids and four had symptoms for three or more years prior to circumcision. There was no clinical or histological relationship with HPV infection, and p16 staining was negative. HPV PCR, performed in two cases, was negative. Basal atypia, insufficient to amount to PeIN, was present in six patients. One patient progressed to PeIN during follow‐up, and no patient progressed to invasive malignancy. Five patients were treated successfully with glans resurfacing and split skin graft reconstruction. Conclusions: Our observations demonstrate that PEKMB represents a form of chronic, undiagnosed or misdiagnosed, inadequately treated or treatment refractory, unstable lichen sclerosus. The significant potential for squamous carcinogenesis (differentiated PeIN and verrucous carcinoma) can be mitigated by timely diagnosis and treatment. Glans resurfacing and split skin graft reconstruction appears to be a successful treatment modality in patients with refractory disease.